Tumbuhan Duku: Senyawa Bioaktif, Aktivitas Farmaklogis dan Prospeknya dalam Bidang Kesehatan - Laila Hanum; Rina S. Kasiamdari (Jurusan Biologi FMIPA Universitas Cenderawasih, 2013)
Lansium domesticum Corr. (Meliaceae) is the popular tropical plant producing economic edible fruits found mainly in Southeast Asia. Seed, leaf, bark, stalks and fruit skin extracts of this plant are potential sources for compounds with broad spectrum of pharmacological activities such as antitumor, anticancer, antimalaria, antimelanogenesis, antibacteria and it may lead to the discovery of a new compouds used for antimutagenic and antioxidative stress. Bioactive compounds, pharmacological activities and prospect this plant in medical application will be discussed in this paper. Key words: Lansium domesticum, bioactive compounds, pharmacological activities, medical application.